Structural and electrochemical characterization of Zr–C–N–Ag coatings deposited by DC dual magnetron sputtering - Velasco, S. Calderon (2014)
ZrCN coatings with incorporated silver were deposited on 316L stainless steel by dual reactive magnetron sputtering to evaluate the silver influence on the structural properties and corrosion resistance of the films. Samples composition was assessed by electron probe microanalysis. Glow discharge optical emission spectroscopy was used to determine the distribution of silver in the films. Structural characterization was performed by X-ray diffraction and Raman spectroscopy. Corrosion resistance was evaluated by potentiodynamic test and electrochemical impedance spectroscopy. Results revealed enhanced corrosion resistance properties of the coated steel and higher coatings reactivity when incorporated with silver, showing a plausible silver release increment.